APPLICATION OF FUZZY COGNITIVE MAPS ON POLICY ANALYSIS: DETERMINING THE POLICY OF SUPPORTING THE ACADEMIC SPIN OFFS - Danny P. Soetanto (Institute of Research and Community Outreach - Petra Christian University, 2002)
Fuzzy Cognitive Map (FCM) is a type of artificial neural network. It can be viewed as a weighted directed graph in which vertices represent concepts and edges represent causal links between them. An FCM can be used as an intelligent decision support system (DSS) tool. It works by representing important issues in a given situation and their causal relationships. The evolution of a dynamic system with time can be simulated and the behavior of the systems can be predicted and explained using an FCM. In this case FCM is used to ditermine the policy to support the academic spin off. Simulation brings forth some conclusions and the best policy can be chosen.